(untitled) (Journal Of Educational and Psychological Researches, 2012)
The study aims at identifying the reasons of weakness in the reading and writing of the primary schools’ pupils at Baghdad governate in Iraq from the educational supervisors’ point of view. The community research contained the educational supervisors of Baghdad governate for the academic year 2011\2012, consisting of a total number of (344), of which (175) were males and (169) were females, where as the sample of the research consisted of (100) educational supervisors. The researcher made up a questionnaire which is consisted of (78) items, distributed over different fields ( the curriculum and the book, methods of teaching, educational technology, the teacher, school environment, the pupil, family circumstances, the school administration and the educational supervisors). Some important results of this study: • Very few school libraries and the negligence of the free reading. • The weak foundation of the pupil in the early stages of primary teaching. • Unavailability of teaching aids specific for teaching Arabic language. • There is no chance to train the pupils on speaking skills as in symposiums. • Rarity of using teaching methods depending upon pupils’ interactions and participations. • Inability of some teachers to control their pupils during classes. • Rarity of teachers specialized in teaching Arabic language that graduated from universities. • The classes are crowded with pupils. • The classes are not suitable for active teaching. • There is a weakness in the academic, educational and professional preparation of teachers.